Implementation of Carbon Capture and Storage in order to Achieve Net Zero Emissions in Indonesia - Raphael Mayaka; Stephen Rodriguez; Ubaidillah Kamal; Muhammad Fikri (Unnes Law Journal, 2024)
In Indonesia, currently many people still use fossil fuels as the main energy source, but with the use of fossil fuels, greater carbon dioxide emissions will be released into the atmosphere, ultimately causing climate change (global warming). To overcome this problem, Indonesia is now starting to adopt techniques that have been used by several countries, namely carbon capture. Carbon Capture and Storage or commonly called CCS or some call it CCUS (Carbon Capture, Utilization and Storage) is one solution to climate change which continues to worsen over time. Indonesia itself is currently preparing 15 projects that will develop and use CO2 capture technology. The research method in the research carried out is using a normative juridical approach. The normative juridical approach is carried out by examining legal principles, legal provisions, legislation and legal mechanisms. Based on the normative type of legal research, several normative approaches are also used, namely the Conceptual Approach and the Statutory Approach. ESDM Ministerial Regulation No. 2 of 2023 does not directly provide benefits to society. This regulation focuses on regulations and incentives for business actors in the upstream oil and gas sector to implement Carbon Capture and Storage (CCS) technology. In Presidential Regulation no. 14/2024 states that holding CCS can be based on three things Carrying out CCS or CCUS implementation in Indonesia begins after obtaining a storage permit for CCS implementation schemes based on permits, whereas for CCS implementation schemes based on cooperation contracts begins when the contractor obtains approval for the proposed field development plan or changes. There are a few things that Indonesia should do such as making a new regulation about funding, insentive and public participation.